Cerebral White Matter and Retinal Arterial Health in Hypertension and Type 2 Diabetes Mellitus - P. L. Yau; R. Hempel; A. Tirsi; A. Convit (International Journal of Hypertension)
We examined 33 hypertensive (22 with comorbid type 2 diabetes mellitus (T2DM)) and 29 normotensive (8 with T2DM) middle-aged and elderly adults, comparable in age and education. Relative to normotensive participants, those with hypertension, in addition to a higher prevalence of periventricular white matter (WM) lesions, had significantly lower WM microstructural integrity of major fiber tracts as seen with MRI-based diffusion tensor imaging. Among participants with hypertension, those with co-morbid T2DM (n=22) had more widespread WM pathology than those without T2DM (n=11). Furthermore and consistent with previous research, both hypertension and T2DM were related to decreased retinal arterial diameter. Further exploratory analysis demonstrated that the observed retinal arteriolar narrowing among individual with hypertension was associated with widespread subclinical losses in WM microstructural integrity and these associations were present predominantly in the frontal lobe. We found that T2DM adds to the damaging effects of hypertension on cerebral WM, and notably these effects were independent of age and body mass index. Given that the decrease in retinal arteriolar diameter may be a biomarker for parallel pathology in cerebral arterioles, our data suggest that the frontal lobe may be particularly vulnerable to microvascular damage in the presence of hypertension and T2DM.